Hubungan Tingkat Pendidikan Ibu Dengan Perkembangan Anak Di Posyandu Mawar Monggang Bantul Yogyakarta Tahun 2022 - Widy Nurwiandani; Desi Ekawati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
Background: The average length of education Indonesia is only 9 years old, it isequivalent to grade 3 junior. In terms of quality of HR (Human Resources) wasapproximately 60% and 80% of junior high school graduates. Establishment of thequality of Human Resources (HR) is optimal, either physically or psychologically dependent on the growth process of children at an early age. The rate of growth anddevelopment at any stage is not the same, depending on heredity, maternaleducation, nutrition consumption, treatment of parents and the child's environment.The behavior of parents,/ mother is one important factor in the sustainability of thegrowth and development of children. Figures health care coverage of children underfive in Puskesmas Sewon 1 achieve the target of above 85%.Objective: To determine the relationship with the mother's educational level of childdevelopment at IHC Mawar Monggang Bantul Yogyakarta in 2022.Methods: This study used observational Analytical methods using cross-sectionalapproach. The population in this study are all mothers of children aged 0-59 monthsin IHC Mawar Monggang village area Bantul, Yogyakarta. The samples in this studyusing total sampling technique to test as many as 69.Then using correlation analysisKendall Tau (τ). The tools used in this study is the data collection questionnaire.Results: The study maternal education level is obtained largely secondary educationwith appropriate child development as many as 35 respondents (83.3%) and 7respondents (16.7%) with a child's development is dubious. The correlationcoefficient is 0523 with a significance of 0.001 (ρ <0.05).Conclusion: There is a positive relationship between the level of education being amother with the development of children aged 0-59 months in IHC Mawar MonggangBantul Yogyakarta in 2022, and statistically meaningfulKeywords: Education Level Mother, Child Development